SCHOOL SHOOTERS: VICTIMS OF UNHEEDED PSYCHOLOGICAL TURMOIL - Cartwright, Duncan (PINS-Psychology in Society, 2025)
Langman, P ( 2009) Why kids kill: Inside the minds of school shooters. New York: Palgrave Macmillan. ISBN 978-0-230-60802-3 hbk. Pages xii + 231. Peter Langman is the director of KidsPeace, an organization that treats at-risk youth. In Why kids kill he brings over 20 years of experience to understanding school shootings and the psychological profile behind such devastating homicidal attacks. He bases his ideas on the case histories of ten school shooters, including the two students who killed 13 people and wounded 23 in the well-known Columbine High School shootings.